USINN: um modelo de interação e navegação orientado à usabilidade - (:unkn) unknown (Universidade Federal do Amazonas, 2017)
The success of an interactive system is strongly related not only to the quality of its user interface, but also to the quality of its interaction and navigation mechanisms. Modeling the interaction and navigation of an interactive system can assist designers in making decisions about how the users will be able to achieve their interaction goals. Besides that, modeling the navigational perspective according to how the user interacts with the application helps to obtain navigational paths with greater usability. However, there is lack of proposals to (1) deal with interaction and navigation through an integrated way and (2) deal with usability features in interaction and navigation modeling. In this dissertation, we propose a usability-oriented interaction and navigation model to improve the quality in use of interactive systems. We evaluate the model through a set of empirical studies with subjects with different levels of experience in using models in industry. Our main contributions are: (1) knowledge base about the existing solutions for the problem, (2) the USINN (Usability-oriented Interaction and Navigation) model, (3) empirical evaluations regarding the USINN ease of use, usefulness, benefits and challenges, (4) the evolution of the USINN notation based on theresults of the empirical studies, and (5) the definition of the USINN metamodel.
Keywords: Modelagem de interação; Modelagem de navegação; Engenharia de software; Design Science; Sistema interativo; CIÊNCIAS EXATAS E DA TERRA: CIÊNCIA DA COMPUTAÇÃO